Bodies in Conflict: The Gendered Impact of War on Women in Hosseini’s A Thousand Splendid Suns and Bashir’s Scattered Souls (Journal of Social Sciences Review, 2025)
When militias and military forces clash in violence it creates war which employs both intrinsic and instrumental weapons. War zones commonly impact males and females to a similar extent based on cultural expectations, but gendering war theory demonstrates women typically endure worse hardships. Women fighting to survive under such adverse conditions experience completely different battles. This research analyzes the war-oriented struggles of Afghan and Kashmiri women using written works by Khaled Hosseini's A Thousand Splendid Suns and Shahnaz Bashir's Scattered Souls. Women in these regions suffer due to the patriarchal systems which war propagates through its context. War creates detrimental disruptions in women's lives which make them face extreme challenges to secure their fundamental needs for shelter and sustenance. This research adopts the feminist theory of war by Sjoberg to study the cultural and social elements of Central Asian war regions as displayed in A Thousand Splendid Suns and Scattered Souls. This comparative research evaluates the day-to-day warfare experiences of women who endure violence and face abduction threats and experience rape besides facing aggressive acts and sustained acts of torture. The analyzed novels depict two different historical situations: the United States military intervention in Afghanistan alongside the Taliban’s ascension as well as Indian occupation of Kashmir. This study demonstrates how women's bodies make them highly vulnerable during wartime in Afghanistan and Kashmir using Sjoberg’s feminist analysis of war and suffering.
Keywords: Afghanistan; Bodies; Gender; Kashmir; War; Women